DEVELOPING ENGLISH SPEAKING MATERIAL FOR STUDENTS OF AUTOMOTIVE ENGINEERING PROGRAM TROUGH TASK-BASED LEARNING AT SMK SINAR HUSNI - Eka Fitria and Masitowarni Siregar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
This study deals with the development of English Speaking Materials for Students of Automotive Engineering Study Program at SMK Sinar Husni. The objective of this study is: to develop appropriate English speaking materials for students of automotive engineering program at SMK Sinar Husni through Task-Based Learning (TBL). The research procedures of this study were Research and Development (R & D) though six stages; Gathering information and data, Analyzing data, Designing the first draft of material, Validating by experts, Rivising and Designing the final product. The subject of this research was class X-1 students of Automotive Engineering study program consisting of 45 students. The instruments for collecting data used in this research were documentary sheet, questionnaire and interview. The result of questionnaire and interview show that students need English speaking materials which appropriate to their major that is Automotive Engineering. Thus, the result of this study was a supplementary material of English speaking through task-based learning which consist of title, objective, let’s start, let’s practice, language reference.The English speaking materials were developed into 3 units of speaking materials. They were then validated by two experts. The average scores are 4,4 from English Lecturer and 4,4 from English Teacher. It means that the developing materials categorized as relevant or appropriate for grade X Students of Automotive Engineering study Program.